INTEGRATED RENEWAL PROCESS - ., Suyono; der Weide, J.A.M. van (IndoMS, 2007)
The marginal distribution of integrated renewal process is derived in this paper. Our approach is based on the theory of point processes, especially Poisson point processes. The results are presented in the form of Laplace transforms.Â DOI :Â http://dx.doi.org/10.22342/jims.13.2.64.149-159